Time varying integration amongst the South Asian equity markets: An empirical study - Sanjay Sehgal; Piyush Pandey; Florent Deisting (Cogent Economics & Finance, 2018)
In this paper, we examine the dynamic nature of equity market integration for the South Asian countries. The daily data for local equity indices are used from 6 January 2004 to 31 March 2015. Copula GARCH models and Diebold and Yilmaz methodology have been employed to study the inter-temporal process of equity market integration. Empirical results show that the sample countries of the region exhibit very little or no levels of integration between them. Equity portfolio flows within the South Asian region reconfirms this trend for low integration in the region. Further, trend analysis of the fundamental determinants of financial integration for the SAARC countries was performed and the same was compared with its neighbouring regional economic bloc in Asia i.e. ASEAN + 6. It indicated that SAARC countries have to show sincere political commitment and require collaboration in efforts of policy realignment to work on their governance parameters, improve on their trade linkages and trade tariffs and develop their equity market infrastructure to achieve higher levels of financial integration. The paper contributes to the International Finance literature, especially dealing with regional economic blocs and has important implications for policy-makers, portfolio managers and academia.
Keywords: C13; C52; F21; F36; G15; 330; stock market integration; SAARC; South Asia; time varying copula; fundamental determinants; equity market development